Development of the accurate localization of partial discharges in medium‐voltage XLPE cables based on pulse reconstruction - Saike Yang (Wiley, 2022)
Abstract A method of reconstructing the original partial discharge (PD) signal to improve the accuracy of PD localization in cross‐linked polyethylene (XLPE) cables is presented here. XLPE cables, extremely sensitive to PDs, are the most popular underground cables in urban grids. The conventional PD localization methods, based on evaluation of the arrival times of PD pulses in the time domain, are negatively affected by the dispersion and attenuation of PD signals propagating in the power cable. A method for the accurate localization of PDs realized through inverse frequency domain modelling (IFDM) is presented here. The method, eliminating the systematic localization error caused by the dispersion and attenuation, significantly improves the localization accuracy. The locations of the PD are identified by comparing peak values of the initial PD signals reconstructed from different extracted pulses. A method for evaluating the propagation constant of the cable is also presented. The efficiency of the accurate localization method was verified by laboratory experiments. Besides, the inherent limitations of the conventional PD localization method for longer cable tests are discussed. The inevitable location error in the conventional methods does not exist in the new method.